Collective memories of colonialism and acculturation dynamics among Congolese immigrants living in Belgium. (January 2018) - Figueiredo, Ana; Oldenhove, Géraldine; Licata, Laurent
Abstract: Collective memories of the historical past allow group members to make sense of their shared past but also to project themselves in the present and future. In this line, collective memories of colonialism may present consequences for present day intergroup relations and acculturation dynamics, given that they allow processes of meaning making and social positioning when different groups with a shared colonial past interact. Indeed, previous research has shown that collective memories are associated with processes of reconciliation, victimization, and group-based emotions, among others, but, to our knowledge, little research has paid attention to the connections between collective memories of colonialism and acculturation dynamics among groups with a past of colonization. The present study aimed to analyze collective memories of colonialism and acculturation experiences among Congolese immigrants living in Belgium. 43 semi-structured interviews with Congolese participants were content analyzed, using an analytical framework along the two variables of interest. We were able to map distinct aspects of the collective memories of colonialism that Congolese immigrants in Belgium have, as well as their experiences of acculturation in Belgium. Our results suggest that individuals remember their ingroup's past in accordance with their current social identifications and relationships within a given society. The results are discussed in light of their consequences for present day intergroup relations between host and immigrant communities in Belgium.